Identifikasi Sebaran Batuan Beku Dengan Metode Tahanan Jenis : Studi Kasus Daerah Desa Siulak Deras, Kecamatan Gunung Kerinci, Kabupaten Kerinci, Provinsi Jambi - Aditya Denny Prabawa; Juventa; Rendi Gustian (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
One of the areas that can be mined for minerals in the form of igneous rocks, such as andesite and basalt, is Siulak Deras Village in Gunung Kerinci Regency, Jambi Province. These rocks are composed of rock minerals and thus do not require international sale. Mining is a relatively straightforward process that does not necessitate the use of sophisticated technology, as it is conducted at the surface. The objective of this research is to gain insight into the distribution of igneous rocks in order to facilitate the interpretation of rock reserves and deposits through the application of the geoelectric resistivity method. The study commenced with the mapping of the geological features pertinent to the excavation of igneous rocks, followed by the planned collection of geoelectrical data utilising a four-track Wenner configuration, with a track length of 240 metres and a track distance of 10 metres. The resistance values thus obtained should be converted into a two-dimensional cross-sectional view. The findings of this research indicate that the area exhibits potential for the presence of igneous rock, as evidenced by resistance values exceeding 2500 Ωm. The distribution of subsurface igneous rocks based on resistivity is thought to occur randomly, as evidenced by geoelectric lines. However, the numbers are very large. The data processing results indicate that the igneous rocks in this area are the result of volcanic activity rather than magma intrusion.